The association between nutritional status and motor development in children under five years old - Nurhayati Masloman; Stefanus Gunawan (Indonesian Pediatric Society Publishing House, 2016)
Background Severe malnutrition in children is closely related to delayed physical growth and mental development. Very few re- ports mention the effects of mild to moderate malnutrition on mo- tor development. Objective The objective of this study was to determine the rela- tionship between nutritional status and motor development in early childhood. Methods In this cross-sectional study, we examined body weight of children under 5 years of age, the ability to sit or walk without support, and parachute sign in those under 2 years of age who came to community child health surveillance posts in Tuminting Subdistrict, Manado, Indonesia. Results Among 359 under-five children, 296 were well-nourished and 63 had mild to moderate malnutrition. The ability to sit without support in malnourished children was significantly delayed com- pared to that in well-nourished ones (P=0.03). The ability to walk without support and parachute sign were not significantly different between the two groups. Conclusion The ability to sit without support in children with mild to moderate malnutrition is delayed compared to that in well-nour- ished ones